PENGARUH LUAS LAHAN TERHADAP PENDAPATAN USAHATANI SEMANGKA DI DESA CIKADU KECAMATAN CIKALONG KABUPATEN TASIKMALAYA - Ane Novianty; Fitri Awaliyah (Universitas Galuh, 2022)
The land is the most important factor of production because the remuneration received by land is higher than other factors of production. The narrowing of land ownership, causing farmers to get smaller profits. This study aims to analyze the effect of land area on watermelon farming income in Cikadu Village, Cikalong District, Tasikmalaya Regency. The research was conducted by a case study on 10 watermelon farmers, with the variables used being land area (X) and farm income (Y). Based on the coefficient of determination analysis, it is known that the influence of land area on farming is 87.42%, which means that land area can affect farm income by 87.42% and its effect on other variables. Furthermore, the results of the linear analysis showed the value of t arithmetic 7.487 > t table 2.306 which means, land area has a positive and significant influence on the income of watermelon farming.